Rancangan Sistem Pengingat Laporan Iranian Optical Distribution Purpose (ODP) - Sutanegara, Made Dimas Dwi; Adi Pramartha, Cokorda Rai (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana), 2019)
PT. Telkom Indonesia is a State-Owned Enterprise (BUMN) that provides the largest telecommunications and network services in Indonesia. Data Access Management (DAMAN) is one of the divisions whose task is to update SISKA data, purify network data, and generate Iranian Optical Distribution Purpose (ODP). ODP functions as a protection or place for fiber optic cables at each Telkom pole. ODP can be viewed through the starclik website, for ODP that is not visible on the platform it could be because full ODP or ODP data is not correct on the server, due to the possibility that the field staff did not report the latest data to the division. So that it requires an ODP reporting reminder system to reduce errors that do not arise from ODP.